Peningkatan Literasi Digital melalui Pemanfaatan Internet di SD Negeri Kedung Jaya 02 - Sri Wahyuni; Purwanto; Deni Sanjaya (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2025)
In education, including at the elementary school level. However, the use of the internet as a learning medium is still suboptimal in some schools, particularly in rural areas. This community service activity aims to improve the digital literacy of teachers and students through training on how to use the internet in learning at Kedung Jaya 02 Elementary School, Bekasi Regency. The methods used included interactive training, internet-based learning simulations, and mentoring during the process of integrating technology into teaching and learning activities. The results of the activity showed an increase in teachers' understanding of using online learning platforms such as Google Classroom and Rumah Belajar, as well as increased student enthusiasm in accessing digital learning resources. Furthermore, a simple internet usage guide module was developed and distributed as an output of the activity. Evaluation showed that this training had a positive impact and was deemed useful by all participants. This activity is expected to be the beginning of a sustainable digital transformation in elementary schools